A polyimide composite film, preparation method and application thereof
The method of preparing a polyimide composite membrane with alternating thermoplastic and thermosetting layers addresses the thermal and mechanical stability issues in FCCL production, achieving improved uniformity and stability for flexible copper-clad laminates.
Patent Information
- Application Number
- CN202411523348.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-30
AI Technical Summary
Existing methods for producing three-layer polyimide (PI) films for flexible copper-clad laminates (FCCLs) face challenges with the thermal stability and uniformity of the intermediate layer due to the use of organic adhesives, which are not suitable for stringent requirements of thermal, mechanical, and dimensional stability.
A method involving the preparation of a polyimide composite membrane with alternating layers of thermoplastic and thermosetting polyimide films, where the thermosetting layer is sandwiched between two thermoplastic layers, using a process involving solution preparation, extrusion, and subsequent stretching and curing to achieve uniformity and stability.
This approach significantly improves the stability and uniformity of the polyimide composite membrane, enhancing the production stability and yield of high-quality flexible copper-clad laminates by minimizing solvent evaporation rate differences and ensuring consistent layer thickness, thus meeting the stringent performance requirements.
Smart Images

Figure CN119036971B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyimide film preparation, and in particular relates to a polyimide composite film, a preparation method and application thereof. Background Art
[0002] Flexible copper clad laminates (FCCLs), as an indispensable material for flexible printed circuits (FPCs), have supported the rapid development of microelectronic applications in recent years and have received widespread attention. Polyimides (PIs) are good candidates for FCCL base film materials because of their excellent thermal, mechanical and electrical properties. There are usually three-layer and two-layer FCCLs. Among them, the three-layer FCCL consists of copper, an organic adhesion promoter (such as epoxy resin) and a PI base film. However, due to the weak heat resistance and relatively low dimensional stability of the organic adhesive, the three-layer FCCL has major defects in thermal stability. Recently, in order to solve these problems, a two-layer FCCL without any adhesive has been developed. However, the requirements for PI performance in the application of two-layer FCCL are quite strict. These requirements include excellent heat resistance, mechanics, dimensional stability and good adhesion properties.
[0003] At present, the methods for making laminated boards for two-layer FCCL mainly include the casting method in which polyamic acid, a precursor of polyimide, is cast on a metal foil and then imidized; the metallization method in which a metal layer is directly provided on a polyimide film by sputtering or plating; and the lamination method in which a polyimide film and a metal foil are bonded together by thermoplastic polyimide. Among these methods, the lamination method has a wider range of metal foil thicknesses than the casting method and a lower device cost than the metallization method, and the lamination method is advantageous in these aspects.
[0004] In the lamination method, a composite film composed of a thermoplastic imide layer having high peel strength on both the upper and lower surfaces of a highly heat-resistant thermosetting polyimide layer is usually laminated with copper foil.
[0005] Traditional methods for producing TPI / PI / TPI composite films mainly include extrusion and coating. The extrusion method is a three-layer co-extrusion of TPI, PI, and TPI, which is formed in one step. The representative company is Kaneka Chemical. The difficulty lies in maintaining the characteristics of each layer, the uniformity of the thickness between layers, the catalyst, and the stability of long-term production. The coating method is to use a coating machine with a high-precision coating head to evenly coat the TPI resin on the thermosetting PI film, and then perform high-temperature heat treatment and imidization to make a three-layer composite film. In the preparation method of the coating method, the middle layer thermosetting PI film needs to undergo secondary imidization, which will cause certain losses to the performance of the film, and the composite film is prone to stratification. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a polyimide composite film, a preparation method and applications thereof.
[0007] A polyimide composite film comprises two identical thermoplastic polyimide layers and a thermosetting polyimide layer, wherein the thermosetting polyimide layer is arranged between the two thermoplastic polyimide layers; a method for preparing the thermoplastic polyimide layer comprises: dissolving a diamine monomer in N,N-dimethylacetamide, stirring; then adding a dianhydride monomer, stirring, dissolving, and obtaining a reaction solution A; adding the dianhydride monomer to the reaction solution A, stirring, obtaining a thermoplastic polyamic acid solution, extruding the thermoplastic polyamic acid solution, casting, drying, expanding, and imidizing, and obtaining a thermoplastic polyimide layer; a method for preparing the thermosetting polyimide layer comprises: dissolving p-phenylenediamine in N,N-dimethylacetamide, stirring, dissolving, and obtaining a reaction solution B; adding the dianhydride monomer to the reaction solution B, stirring, obtaining a thermosetting polyamic acid solution, extruding the thermosetting polyamic acid solution, casting, drying, expanding, and imidizing, and obtaining a thermosetting polyimide layer.
[0008] A method for preparing a polyimide composite film comprises the following steps:
[0009] (1) preparing a thermoplastic polyamic acid solution, dissolving a diamine monomer in N,N-dimethylacetamide and stirring; then adding a dianhydride monomer, stirring and dissolving to obtain a reaction solution A; adding the dianhydride monomer to the above reaction solution A and stirring to obtain a thermoplastic polyamic acid solution;
[0010] (2) preparing a thermosetting polyamic acid solution, dissolving p-phenylenediamine in N,N-dimethylacetamide, stirring and dissolving to obtain a reaction solution B; adding a dianhydride monomer to the reaction solution B, stirring and obtaining a thermosetting polyamic acid solution;
[0011] (3) Extruding the thermoplastic polyamic acid solution and the thermosetting polyamic acid solution prepared above, and performing casting, drying, expanding and imidization to obtain a polyimide composite film having a thermosetting polyimide layer and two thermoplastic polyimide layers; the thermosetting polyimide layer is arranged between the two thermoplastic polyimide layers.
[0012] Preferably, the stirring time in step (1) and step (2) is 1 hour.
[0013] Preferably, the viscosity of the thermosetting polyamic acid solution and the thermoplastic polyamic acid solution are both 30,000 to 150,000 mPa·s.
[0014] Preferably, the solid contents of the thermosetting polyamic acid solution and the thermoplastic polyamic acid solution are both 10-30 wt %.
[0015] Preferably, the drying temperature is 120°C to 180°C.
[0016] Preferably, the diamine monomer comprises
[0017] One or more of .
[0018] Preferably, the dianhydride monomer comprises
[0019] One or more of .
[0020] Preferably, the thickness ratio of any one of the thermoplastic polyimide layers and the thermosetting polyimide layer is 1:1-1:5.
[0021] The polyimide composite film prepared by the preparation method or the application of the polyimide composite film in the production of flexible copper-clad laminates.
[0022] The beneficial effects that can be achieved by the present invention are:
[0023] The polyimide composite film prepared by the above method greatly improves the A / B surface problem caused by the different solvent evaporation rates on the upper and lower surfaces of the thermoplastic-thermosetting-thermoplastic polyimide composite film and the problem of uneven thickness between polyimide layers when preparing ultra-thin polyimide composite films, thereby improving the production stability and yield rate of the polyimide composite film. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 The present invention is a schematic diagram of a process for producing a polyimide composite film.
[0026] Figure 2 This is an electron microscope image of the polyimide composite film prepared in the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] In the present invention, an extrusion-cast coating method is used. The extrusion-cast coating method is a method for manufacturing a film including the following steps: a polyamic acid solution is extruded from a single-channel die head onto a self-supporting body, after casting and drying, thermal imidization is carried out in a high-temperature oven. As a casting device, a known device can be used. As an example of a casting device, a rotating roller, a rotating belt, a moving plate, etc. can be cited, but it is not limited thereto. Considering the ease of introducing a drying process after casting, a rotating belt is preferably used. As the material of a rotating roller, a rotating belt, and a moving plate, metal, cloth, resin, glass, magnetic device, etc. can be used. From the aspect of the structural stability of the film, metal is preferred, and from the aspect of the ease of stripping the film and the corrosion resistance, stainless steel is most preferred. And then, in order to further improve the stripping property and corrosion resistance of the film, the plating of chromium, nickel, or tin can be carried out on the surface of the rotating roller, rotating belt, and moving plate made of metal.
[0029] The liquid film formed by casting is formed into a gel-like film after drying in a drying furnace. In the present invention, a known drying furnace can be used as a drying furnace. Examples of drying furnaces include hot air drying furnaces, infrared drying furnaces, etc., but are not limited thereto. From the perspective of effectively drying the solvent, a hot air drying furnace is preferred. When the drying temperature is too low, it cannot be fully dried, and when it is too high, the contained solvent boils, sometimes hindering the formation of a smooth film. In particular, tiny defects are easily generated on thin surface layers that serve as adhesive layers such as thermoplastic polyimide layers. Therefore, the drying temperature is preferably less than the boiling point of the solvent used + 50°C. Specifically, it is preferably 80°C to 200°C, and more preferably 120°C to 180°C. By volatilizing at least a portion of the solvent, a self-supporting multilayer film can be obtained.
[0030] The film after drying in the above-mentioned drying furnace still has residual solvent and the imidization reaction has not been fully carried out, so it is further dried in a firing furnace to allow the imidization reaction to be fully carried out. As a firing furnace, a known firing furnace can be used. As examples of firing furnaces, hot air firing furnaces, infrared firing furnaces, etc. can be cited, but are not limited to these. It is preferred to use these firing furnaces in combination according to the degree of firing. It is preferred to heat with a hot air firing furnace at 100 to 500°C and then heat with an infrared firing furnace at 300°C to 600°C. There is no uniform limitation on the time of imidization, as long as sufficient time is taken for imidization and drying to be substantially completed, which is generally appropriately set in the range of about 10 to 1800 seconds.
[0031] The multilayer film introduced into the firing furnace can be kept on the support or peeled off from the support. In addition, in order to improve the melt flowability of the thermoplastic layer, the imidization rate can be intentionally reduced or the solvent can be left to remain. This can improve the adhesion with conductors such as copper foil.
[0032] The thermoplastic layer-thermosetting layer-thermoplastic layer polyimide composite film obtained by the above preparation method, the thickness of the thermoplastic polyimide layer of the three-layer polyimide composite film is 2 μm to 10 μm; the thickness of the thermosetting polyimide layer is 4 μm to 40 μm; Figure 2 As shown, among all the layers of the three-layer polyimide composite film, there is no difference in characteristics between the polyimide layer directly contacting the support and the polyimide layer on the opposite side of the three-layer polyimide composite film, the peel strength difference of the A / B surface is <0.5 N / cm, and a polyimide composite film with a deviation of the film thickness composition rate in the film width direction of -4% to 4% can be prepared, which can meet the current requirements for the performance of the two-layer flexible copper clad laminate base film.
[0033] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0034] First, some synthesis examples of the thermoplastic polyamic acid solution and the thermosetting polyamic acid solution used in the following embodiments are given:
[0035] Synthesis of thermoplastic polyamic acid solution:
[0036] Synthesis example 1:
[0037] Dissolve 2.05 kg of 2,2'-bis[4-(4-aminophenoxyphenyl)]propane (BAPP) and 1.00 kg of 4,4'-diaminodiphenyl ether (ODA) in 25.56 kg of N,N-dimethylacetamide (DMAc) and stir for 1 hour to dissolve. Add 1.47 kg of biphenyltetracarboxylic dianhydride (s-BPDA) to it and stir for 1 hour to dissolve. Slowly add 1.09 kg of pyromellitic dianhydride (PMDA) to the above reaction solution and stop adding when the viscosity reaches about 35000 mPa·s. Stir for 1 hour to obtain a polyamic acid solution (hereinafter referred to as PAA-1) as a precursor of the thermoplastic polyimide layer with a solid content concentration of 18% by weight and a rotational viscosity of 35000 mPa·s at 23°C.
[0038] Synthesis example 2:
[0039] 1.46 kg of 1,3-bis(4'-aminophenoxy)benzene (TPE-R) and 1.00 kg of 4,4'-diaminodiphenyl ether (ODA) were dissolved in 25.24 kg of N,N-dimethylacetamide (DMAc), and stirred for 1 hour to dissolve. 1.47 kg of biphenyltetracarboxylic dianhydride (s-BPDA) was added thereto, and stirred for 1 hour to dissolve. 1.61 kg of 3,3',4,4'-benzophenonetetracarboxylic dianhydride (BTDA) was slowly added to the above reaction solution, and the addition was stopped when the viscosity reached about 35000 mPa·s. Stirring for 1 hour, a polyamic acid solution (hereinafter referred to as PAA-2) as a precursor of a thermoplastic polyimide layer having a solid content concentration of 18 wt % and a rotational viscosity of 35000 mPa·s at 23°C was obtained.
[0040] Synthesis of thermosetting polyamic acid solution:
[0041] Synthesis example 3:
[0042] Dissolve 2.70 kg of p-phenylenediamine (PDA) in 45.78 kg of N,N-dimethylacetamide (DMAc) and stir for 1 hour to dissolve it. Slowly add 7.35 kg of biphenyltetracarboxylic dianhydride (s-BPDA) to the above reaction solution, and stop adding when the viscosity reaches about 40,000 mPa·s. Stir for 1 hour to obtain a polyamic acid solution (hereinafter referred to as PAA-3) as a precursor of a thermosetting polyimide layer with a solid content concentration of 18% by weight and a rotational viscosity of 40,000 mPa·s at 23°C.
[0043] Synthesis example 4:
[0044] Dissolve 2.05 kg of 2,2'-bis[4-(4-aminophenoxyphenyl)]propane (BAPP) and 1.00 kg of 4,4'-diaminodiphenyl ether (ODA) in 25.56 kg of N,N-dimethylacetamide (DMAc) and stir for 1 hour to dissolve. Add 1.47 kg of biphenyltetracarboxylic dianhydride (s-BPDA) to it and stir for 1 hour to dissolve it. Slowly add 1.09 kg of pyromellitic dianhydride (PMDA) to the above reaction solution and stop adding when the viscosity reaches about 120000 mPa·s. Stir for 1 hour to obtain a polyamic acid solution (hereinafter referred to as PAA-4) as a precursor of the thermoplastic polyimide layer with a solid content concentration of 18% by weight and a rotational viscosity of 120000 mPa·s at 23°C.
[0045] Synthesis example 5:
[0046] Dissolve 2.70 kg of p-phenylenediamine (PDA) in 45.78 kg of N,N-dimethylacetamide (DMAc) and stir for 1 hour to dissolve it. Slowly add 7.35 kg of biphenyltetracarboxylic dianhydride (s-BPDA) to the above reaction solution, and stop adding when the viscosity reaches about 130,000 mPa·s. Stir for 1 hour to obtain a polyamic acid solution (hereinafter referred to as PAA-5) as a precursor of a thermosetting polyimide layer with a solid content concentration of 18% by weight and a rotational viscosity of 130,000 mPa·s at 23°C.
[0047] Example 1
[0048] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 1 and Synthesis Example 3 were sequentially extruded and cast on a casting roll using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150° C. for 300 seconds to obtain a three-layer self-supporting film having self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400° C. for 600 seconds, thereby performing thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 2.0 μm / 8.5 μm / 2.0 μm of thermoplastic polyimide layer / thermosetting polyimide layer, as shown in FIG. Figure 1 shown.
[0049] Example 2
[0050] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 2 and Synthesis Example 3 were extruded and cast on a casting roll in sequence using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150°C for 300 seconds to obtain a three-layer self-supporting film with self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds to perform thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 2.0 μm / 8.5 μm / 2.0 μm for thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0051] Example 3
[0052] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 1 and Synthesis Example 3 were extruded and cast on a casting roll in sequence using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150°C for 300 seconds to obtain a three-layer self-supporting film with self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds, thereby performing thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 5.0 μm / 15 μm / 5.0 μm of thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0053] Example 4
[0054] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 2 and Synthesis Example 3 were extruded and cast on a casting roll in sequence using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150°C for 300 seconds to obtain a three-layer self-supporting film with self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds to perform thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 5.0 μm / 15 μm / 5.0 μm for thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0055] Example 5
[0056] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 4 and Synthesis Example 5 were extruded and cast on a casting roll in sequence using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150°C for 300 seconds to obtain a three-layer self-supporting film with self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds to perform thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 5.0 μm / 5.0 μm / 5.0 μm of thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0057] Example 6
[0058] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 4 and Synthesis Example 5 were extruded and cast on a casting roll in sequence using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150°C for 300 seconds to obtain a three-layer self-supporting film with self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds to perform thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 5.0 μm / 15 μm / 5.0 μm for thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0059] Example 7
[0060] The thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained in Synthesis Example 4 and Synthesis Example 5 were extruded and cast on a casting roll in sequence using a single-channel die head with a die lip width of 200 mm; then, the thermoplastic-thermosetting-thermoplastic three-layer composite film was heated at 150°C for 300 seconds to obtain a three-layer self-supporting film with self-supporting properties, and the three-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds to perform thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 2.0 μm / 10.0 μm / 2.0 μm of thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0061] Comparative Example 1
[0062] A multi-flow channel 3-layer co-extrusion 3-layer die with a die lip width of 200 mm was used for extrusion, so that the thermoplastic polyamic acid solution obtained in Synthesis Example 1 and the thermosetting polyamic acid solution obtained in Synthesis Example 3 were sequentially cast on a casting roll into a three-layer structure, wherein the thermoplastic polyamic acid solution was in contact with the casting roll, and the thermosetting polyamic acid solution was on its upper surface. Then, the three-layer film was heated at 150 ° C for 300 seconds to obtain a 3-layer self-supporting film, and the 3-layer self-supporting film was fixed to a metal frame, expanded, and then dried at 400 ° C for 600 seconds, thereby performing thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 5.0 μm / 15.0 μm / 5.0 μm of thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0063] Comparative Example 2
[0064] A double-sided coating device was used to prepare a polyimide film from the thermosetting polyamic acid solution obtained in Synthesis Example 3 as a base film (15 μm), and the thermoplastic polyamic acid solution obtained in Synthesis Example 1 was double-sidedly coated on the upper and lower surfaces of the base film. Next, the three-layer film was heated at 150°C for 300 seconds to obtain a three-layer composite film in which the middle layer was a thermosetting polyimide film and the upper and lower layers were thermoplastic polyamic acid gel films, and the three-layer composite film was fixed to a metal frame, expanded, and then dried at 400°C for 600 seconds, thereby performing thermal imidization, thereby obtaining a three-layer polyimide composite film with a thickness of 5.0 μm / 15.0 μm / 5.0 μm of thermoplastic polyimide layer / thermosetting polyimide layer / thermoplastic polyimide.
[0065] Performance Testing
[0066] 1. Static Thermomechanical Analysis Experimental Method
[0067] Static thermomechanical analysis (TMA): American TA Instruments TMA Q400EM static thermomechanical analyzer (room temperature to 400°C, 5°C / min).
[0068] 2. Mechanical properties test experimental method
[0069] INSTRON 5567 universal strength testing machine, tensile rate 5mm / min, test temperature is room temperature (about 23°C), initial fixture span is about 20mm, sample size is about 0.025mm thick, 15mm wide and 100mm long.
[0070] 3. Peel strength test method
[0071] INSTRON 5567 universal strength testing machine, tensile rate 5mm / min, test temperature is room temperature (about 23℃), the film and copper foil are hot pressed and then subjected to 180° peeling tensile test, the data processing is as follows:
[0072] L M =Minimum load
[0073] W S = measured width of the peel strip
[0074] The properties of the products obtained in Synthesis Examples 1 to 5 were measured and the results are shown in Table 1.
[0075] Table 1 Comparison of properties of products obtained from Synthesis Examples 1 to 5
[0076]
[0077] The properties of the products obtained in Examples 1 to 7 and Comparative Examples 1 to 2 were measured, and the results are shown in Table 2.
[0078] Table 2 Performance comparison of the products obtained from Examples 1 to 7 and Comparative Examples 1 to 2
[0079]
[0080] From Table 2, Examples 1 and 2 show that as the proportion of flexible monomers increases, the glass transition temperature of the thermoplastic layer will decrease and the peel strength will increase. Compared with Examples 1 and 2, the overall film thickness of Examples 3 and 4 increases, but the peel strength decreases, which may be related to the fact that heat cannot be transferred in time during hot pressing to melt the entire thermoplastic layer. Similarly, from Comparative Examples 5 and 7, it can be seen that the peel strength of composite films with different thickness ratios also maintains the above trend, and as the proportion of the thickness of the intermediate thermosetting layer increases, the overall tensile strength of the film increases significantly. Comparative Examples 3 and 6 show that as the viscosity of the PAA solution increases, the overall tensile strength of the composite film increases significantly. The data from Comparative Example 1 show that although the TPI composite film prepared by three-layer co-extrusion maintains good mechanical properties, the peel strength has a large difference between the A / B sides, and the thickness composition rate deviation is also too large. The TPI composite film prepared by the double-sided coating method in Comparative Example 2 has an overall decrease in peel strength and tensile strength. Therefore, in general, the thickness of each layer of the polyimide composite film prepared in Examples 1 to 7 is uniform and controllable, and an ultra-thin TPI composite film can be prepared, and the deviation of the film thickness composition ratio in the film width direction is -4% to 4%, and the difference in peel strength of the A / B surface is <0.5 N / cm. The current requirements for the performance of the base film of the two-layer flexible copper clad laminate are met.
[0081] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0082] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.
Claims
1. A method for preparing a polyimide composite film, characterized in that: The polyimide composite film comprises two identical thermoplastic polyimide layers and a thermosetting polyimide layer, wherein the thermosetting polyimide layer is arranged between the two thermoplastic polyimide layers; The preparation method of the thermoplastic polyimide layer comprises: dissolving a diamine monomer in N,N-dimethylacetamide, stirring; then adding a dianhydride monomer, stirring, dissolving, and obtaining a reaction solution A; adding the dianhydride monomer to the reaction solution A, stirring, obtaining a thermoplastic polyamic acid solution, extruding the thermoplastic polyamic acid solution, casting, drying, expanding, and imidizing, and obtaining a thermoplastic polyimide layer; The preparation method of the thermosetting polyimide layer comprises: dissolving p-phenylenediamine in N,N-dimethylacetamide, stirring, dissolving, and obtaining a reaction solution B; adding the dianhydride monomer to the reaction solution B, stirring, obtaining a thermosetting polyamic acid solution, extruding the thermosetting polyamic acid solution through a single-channel die head, casting, drying, expanding, and imidizing, and obtaining a thermosetting polyimide layer; The viscosity of the thermosetting polyamic acid solution and the thermoplastic polyamic acid solution are both 30000-150000 mPa·s, and the thickness ratio of the thermoplastic polyimide layer to the thermosetting polyimide layer is 1:1-1:5; The preparation method of the polyimide composite film comprises the following steps: (1) preparing a thermoplastic polyamic acid solution, dissolving a diamine monomer in N,N-dimethylacetamide and stirring; then adding a dianhydride monomer, stirring, and dissolving to obtain a reaction solution A; adding the dianhydride monomer to the reaction solution A and stirring to obtain a thermoplastic polyamic acid solution; (2) preparing a thermosetting polyamic acid solution, dissolving p-phenylenediamine in N,N-dimethylacetamide, stirring and dissolving to obtain a reaction solution B; adding a dianhydride monomer to the reaction solution B, stirring and obtaining a thermosetting polyamic acid solution; (3) using a single-channel die head for extrusion, the thermoplastic polyamic acid solution and the thermosetting polyamic acid solution obtained above are sequentially extruded onto a casting roller for casting, drying, widening and imidization to obtain a polyimide composite film having a thermosetting polyimide layer and two thermoplastic polyimide layers; the thermosetting polyimide layer is arranged between the two thermoplastic polyimide layers.
2. The method for preparing a polyimide composite film according to claim 1, characterized in that: The stirring time in step (1) and step (2) is 1 hour.
3. The method for preparing a polyimide composite film according to claim 1, characterized in that: The viscosity of the thermosetting polyamic acid solution and the thermoplastic polyamic acid solution are both 30000-150000 mPa·s.
4. The method for preparing a polyimide composite film according to claim 1, characterized in that: The solid contents of the thermosetting polyamic acid solution and the thermoplastic polyamic acid solution are both 10-30 wt %.
5. The method for preparing a polyimide composite film according to claim 1, characterized in that: The drying temperature is 120°C to 180°C.
6. The method for preparing a polyimide composite film according to claim 1, characterized in that: The diamine monomer includes One or more of .
7. The method for preparing a polyimide composite film according to claim 1, characterized in that: The dianhydride monomer includes One or more of .
8. The method for preparing a polyimide composite film according to claim 1, characterized in that: The thickness ratio of any one of the thermoplastic polyimide layers and the thermosetting polyimide layer is 1:1-1:
5.
9. Use of the polyimide composite film obtained by the preparation method according to any one of claims 1 to 8 or the polyimide composite film according to claim 1 in the production of flexible copper-clad laminates.
Citation Information
Patent Citations
Polyimide composite film with low moisture absorption rate and low thermal expansion coefficient, preparation method, thermosetting polyamic acid and thermosetting polyamic acid solution
CN115368566A
Manufacturing method of adhesive film
JP2005305968A